Computational and experimental validation of morin as adenosine deaminase inhibitor. (4th May 2018) - Arun, K. G.; Sharanya, C. S.; Sadasivan, C.
Abstract: Adenosine deaminase (ADA) is one of the major enzymes involved in purin metabolism, it has a significant role in cell growth and differentiation. Over-activity of ADA has been noticed in some pathology, like malignancy and inflammation and makes it an attractive target for the development of drugs for such diseases. In the present study, ADA inhibitory activity of morin, a bioactive flavonoid, was assessed through computational and biophysical methods. The enzyme kinetics data showed that morin is a competitive inhibitor of ADA. Binding energy calculated from ITC analysis was −7.11 kcal/mol. Interaction of morin with ADA was also studied using fluorescence quenching method. Molecular docking studies revealed the structural details of the interaction. Molecular dynamics study in explicit solvent was also conducted to assess the structural stability of protein ligand complex.